2022
DOI: 10.1371/journal.pone.0272305
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in rates of permanent pacemaker implantation and in-hospital complications: A statewide cohort study of over 7 million persons from 2009–2018

Abstract: Background Whether a bias exists in the implantation of permanent pacemakers (PPI) and complications according to sex and age in the Australian population is unclear. Hypothesis Population rate of PPI and its complications differed between men and women. Methods We examined the prevalence of PPI from January-2009 to December-2018 from datasets held by the New South Wales (NSW) Centre-for-Health-Record-Linkage, including patient’s characteristics and in-hospital complications. All analysis was stratified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
5
1
Order By: Relevance
“…We reported an upper limb DVT rate of 1.7%, which was lower than studies conducted in Brazil (6%) and Iran (21%), but was greater than the one from Australia (0.15%). 10 , 29 , 30 Prior reports used different imaging modality approaches, and types of cardiac rhythm management devices, which could be the cause of this significant variation in studies results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We reported an upper limb DVT rate of 1.7%, which was lower than studies conducted in Brazil (6%) and Iran (21%), but was greater than the one from Australia (0.15%). 10 , 29 , 30 Prior reports used different imaging modality approaches, and types of cardiac rhythm management devices, which could be the cause of this significant variation in studies results.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found a death rate that was higher than studies conducted in Australia (0.73%), Iraq (0%), the USA (0.08%), and Kenya (0.0%), but lower than those conducted in Senegal (1.2%), Spain (5.2%), and France (3.9%). 9 , 10 , 13 , 15 , 20 , 23 , 33 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The survival at 30 years on from the implantation of permanent pacemakers seems to be higher in women than in men but no univocal data are available on life quality [28]. Periprocedural side effects (pneumothorax, cardiac perforation, and pocket hematoma) occur more frequently in women than in men [92,166] and, vice-versa, infective complications seem to be more frequent in men, but the data are non-univocal [28]. One reason could be the fact that women receive a pacemaker at an older age and for a longer time, given their longer life expectancy [92,166].…”
Section: The Cardiovascular (Cv) System Where Sex-gender-based Medici...mentioning
confidence: 99%